Modifikasi Materi Pratikum (Karbohidrat-Enzim) untuk Meningkatkan Pemahaman Konsep Biokimia Secara Komprehensif dan Efisien - Wijayanti, Titik; Lestari, Purwaning Budi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
Main objectives of this research are to analysis the increase in understanding biochemistry concepts comprehensively caused by practice concept modification (Carbohydate-Enzyme) and analysis the efficiency of practical activities caused by practice concept modification (Carbohydate-Enzyme). Research conducted in September through November 2015 are analytical descriptive research, there are 80 students as respondents were devided into 2 groups of treatment, namely group A as group with practice module that has not been modified and group B with practice module that have been modified. Paired t test result showed that group with practice module were modified to get the score of post-test evaluation better and significantly different than group with practice module that has not been modified. The validation result of practice module by students, instucture, material experts and media experts showed that practice module modified is eligible to used as practical module in the future.